(untitled) (Research, Society and Development, 2022)
The objective was to characterize the fermentative profile, nutritional and microbiological value of in natura cassava root silage with and without additives. A completely randomized design was used in a 4x3 split-plot scheme, with five replications. The study materials were allocated to the plots: Ground cassava root in natura or added to corn, soybean or rice bran. In the subplots, the times were allocated: fresh material: before ensiling, opening: at 45 days of fermentation and stability after the silage was exposed to air for seven days. Sampling was carried out to determine the bromatological analysis, total digestible nutrients, digestibility, pH, temperature, ammoniacal nitrogen, the microbiological profile through the determination of the populations of fungi and yeasts, Clostridium, lactic acid bacteria and enterobacteria. The addition of bran changed the parameters evaluated. The dry matter increased during fermentation and exposure to air and in all times and materials the pH was adequate. Crude protein decreased until the opening of the silos due to unwanted fermentations, being higher in the silage added with soybean meal. The low content of fibrous compounds and TDN, and the high digestibility suggest silages obtained as energy feed in ruminant and/or monogastric diets. In conclusion, cassava root in natura or with the inclusion of additives can be preserved in the form of silage for use in ruminant diets.